PSI-20 The effect of ewe gastrointestinal nematode burden during the periparturient period on lamb growth - Mosichuk, Allison (J Anim Sci, 2019)
Research evaluating the effects of ewe gastrointestinal nematode infection (GNI) during the periparturient period (PPR) on offspring growth is limited. We hypothesized ewes with a greater parasite burden during the PPR will negatively impact birth and weaning weight. Packed cell volume (PCV) was measured in ewes (2018, n = 11) at 3 weeks pre-partum (-3), birth, 3 (+3) and 6 (+6) wks postpartum. Lamb birth weight, weaning weight (WW), and ADG (birth - 8 weeks) were collected. Ewes in the upper 50% (n = 5–6) and lower 50% (n = 5–6) for PCV were classified as either HIGH and LOW at each time period. Data were analyzed in SAS using proc mixed (significance P ≤ 0.05). PCVs for LOW and HIGH ewes were (mean ± SEM) 27% ± 0.2% vs 30% ± 0.8% at -3, 28% ± 0.3% vs 32% ± 0.4% at birth, 24% ± 0.4% vs 29% ± 0.6% at +3, and 25% ± 0.2% vs 30% ± 1.0% at +6 respectively. Post-partum, lambs reared by LOW ewes exhibited reduced ADG (0.69 ± 0.03 kg/d vs 0.81 ± 0.03 kg/d; P = 0.02) and WW (29.34 kg ± 1.41 kg vs 33.64 kg ± 1.47 kg; P = 0.04) compared to lambs reared by HIGH ewes. Lambs reared by LOW ewes at +3 exhibited reduced ADG versus lambs reared by HIGH ewes (0.69 ± 0.034 kg/d vs. 0.81 ± 0.034 kg/d; P = 0.02). No effect of maternal PCV on birth weight or WW, at -3, birth, or +6 was observed on offspring birth weight, WW, or ADG (P ≥ 0.13). In conclusion, the effects of PPR GNI appear to be postnatal.